The Effect of Service Quality and Brand Image on Revisit Intention at The Premiere Hotel Pekanbaru - Reza Mayrah Wati; Kurnia Illahi Manvi; Iqbal Harifal (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the influence of service quality and brand image on guests’ revisit intention at The Premiere Hotel Pekanbaru amid fluctuating repeat guest rates, increasing hotel competition, and complaints concerning service, facilities, and guest experience. Research Method: A quantitative causal-associative design was employed. The population comprised 12,680 repeat guests who stayed at the hotel from January to December 2025. Using the Slovin formula, 100 respondents were selected through purposive sampling. Data were collected through structured questionnaires using a five-point Likert scale and analyzed with descriptive statistics, classical assumption tests, and multiple linear regression. Results and Discussion: Service quality and brand image each have a positive and significant effect on revisit intention. Simultaneously, both variables significantly influence revisit intention and explain 89.3% of its variance (R² = 0.893). These findings confirm that improved service quality and a stronger brand image encourage guests to revisit the hotel. Implications: Hotel management should improve employee responsiveness, reliability, assurance, empathy, physical facilities, service consistency, and marketing effectiveness to strengthen guest trust, satisfaction, and intention to revisit. Originality: This study provides empirical evidence from repeat guests of a four-star hotel in Pekanbaru and offers practical insights into strengthening revisit intention through service quality and brand image.